Developing Literacy Skills through Mentoring Management as an Actualization of Children's Potential - Ira Evikasari; Hardita Arum Pramesti; Ardha Ilham Wijanarko; Rohmad Wahid Rhomdani (Al'Adzkiya Journal, 2023)
The purpose of this study was to produce a magazine product to inform readers about the method used by SMP Muhammadiyah 1 Jember in developing students' literacy skills, especially work skills that will be displayed in the school bulletin. The method used is science and technology diffusion, which is a program that is carried out by producing a product for the target group. The resulting product is a school bulletin at SMP Muhammadiyah 1 Jember. Education and literacy skills are two important things in life; the progress of a country directly depends on the level of literacy in that environment. This study will describe strategies for improving literacy skills and the results of increasing magazine literacy. By carrying out magazine literacy activities carried out by KKN-Dik students, it is hoped that students will be able to channel their critical thinking skills and be able to communicate well. This can also be expressed through writing, drawing, making a product, or other work.